Sperm activating odorous substances in human follicular fluid and vaginal secretion: Identification by gas-chromatography-olfactometry and CA2+-imaging - Hartmann, Constanze; Triller, Annika; Spehr, Marc; Dittrich, Ralf; Hatt, Hanns; Büttner, Andrea (ChemPlusChem, 2013)
Human sperm chemotaxis to follicular fluid has been well established, but the molecular mechanism(s) for this phenomenon are still largely unclear. Studies indicate that odorant receptors expressed on spermatozoa could play a role in this scenario. It has recently been shown that several synthetic floral scents activate the receptors OR1D2, OR4D1, and OR7A5 in vitro and evoke distinct sperm motility patterns in vivo. However, all agonists found so far are of synthetic origin and, thus, the presence of endogenous structural analogues in female bodily fluids is subject to speculation. Therefore, the aim of the study reported herein was to investigate the occurrence of odor compounds in vaginal secretions and follicular fluid by using gas chromatography- olfactometry. Chemically identified constituents of either bodily fluid were then analyzed for activation of recombinant chemoreceptors and candidate ligands were further tested for induction of sperm Ca2+ signals. Through using this approach, two novel odorant receptor-ligand pairs are reported and human sperm Ca2+ elevations in response to both odorous substances, namely 5α-androst-16-en-3-one and 4-hydroxy-2,5-dimethyl-3(2H)-furanone, are shown. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-04-14:Pub.2013.nat.dchph.llmch.sperma
Keywords: biological activity; calcium signaling; gas chromatography-olfactometry; membrane proteins; receptors